Pengaruh Net Profit Margin, Debt Equity Ratio, Dan Firm Size Terhadap Manajemen Laba Pada Perusahaan Telekomunikasi yang Terdaftar Di Bursa Efek Indonesia Periode 2008-2017 - Hervando Putra (Universitas Batanghari Jambi, 2019)
The title of this research is The Effect of Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Firm Size on Earning Management in The Telecommunications Company Listed On The Indonesia Stock Exchange (BEI) for the Period 2012-2016. With an average of Net Profit Margin (NPM) is 187% Debt to Equity Ratio is 11%, the average of Firm Size is 1%, and the average ManajemenLaba is 1,43%. The research aims to get the result and analyst about the effect of Net Profit Margin, Debt Equity Ratio, and Firm Size on Earning Management in The Telecomunications Company with Simultaneous and Partial. Method of Analysis used is multiple linear regression analysis, the classical assumption (Normality, multicollinearty, heterocedasity, and autocorrelation) hypothesis testing (F test and test) and the coefficient of determination. After that the research’s data processed by using SPSS version 20.0 aplication for windows. Telecommunications companies are to meet the needs of telecommunications using telecommunications networks. Telecommunication comanies in Indonesia offer mobile telephone services, cellular telephone services, interconnection services, short message services, facsimile services, cellular internet service, and video calls. In this study the author took sample telecommunications componies consisting of :PT. XL Axiata Tbk (EXCL), and PT. Telekomunikasi Indonesia Tbk (TLKM).